STUDI EFISIENSI INJEKSI SURFACTANT SECARA HORIZONTAL DENGAN MEMPERTIMBANGKAN KETEBALAN ZONA PRODUKSI - Reza, Muhammad
Surfactant injection into reservoir is an enhanced oil recovery method which grows continually as it has been proven for significantly mobilizing trapped oil in the reservoir. The condition of injector well in the reservoir gives important influence on sweep efficiency of surfactant injection as well as the chemical composition of the surfactant itself. Horizontally surfactant injection has been simulated in this study to observe its effectiveness in improving recovery factor by considering the influence of oil zone thickness. Simulation results showed that oil recovery factor yielded by injecting surfactant is comparatively higher for injection in relatively thin zone. In this thin zone, however, surfactant contribution on oil recovery factor is just slighly better than injecting water while in relatively thick zone, surfactant injection gives considerably better recovery factor compared to water-injection only for the entire life of the field. By making various scenarios of production as considering change in production zone thickness, then a mathematical equation can be developed to determine oil recovery factor in horizontally surfactant injection as a function of production zone thickness as to be a medium for predicting the efficiency of horizontally surfactant injection at certain thickness.